The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.clinbiomech.2012.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of forces acting on implant rods and degree of scoliosis correction

Abstract: Background: Adolescent idiopathic scoliosis is a complex spinal pathology characterized as a threedimensional spine deformity combined with vertebral rotation. Various surgical techniques for correction of severe scoliotic deformity have evolved and became more advanced in applying the corrective forces. The objective of this study was to investigate the relationship between corrective forces acting on deformed rods and degree of scoliosis correction. Methods: Implant rod geometries of six adolescent idiopathi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 18 publications
(14 reference statements)
1
33
0
Order By: Relevance
“…High implant density has not shown improvement in patient reported outcomes [38][39][40][41][42][43][44] or cosmesis [39], and has contributed to less thoracic kyphosis [38,40,41], and high costs [42,45]. In contrast to what might be expected, it was shown through a finite element analysis and computational study that high implant density does not improve the distribution of forces and correction [46,47].…”
Section: Supporting Empirical Evidencementioning
confidence: 95%
“…High implant density has not shown improvement in patient reported outcomes [38][39][40][41][42][43][44] or cosmesis [39], and has contributed to less thoracic kyphosis [38,40,41], and high costs [42,45]. In contrast to what might be expected, it was shown through a finite element analysis and computational study that high implant density does not improve the distribution of forces and correction [46,47].…”
Section: Supporting Empirical Evidencementioning
confidence: 95%
“…3D-CAD model of rod geometry was generated and Finite Element Analysis (FEA) was performed using ANSYS 11.0 according to the previously developed method reported by Salmingo et al [ 12 , 13 ]. Material properties of this rod are Young's Modulus (E), yield stress (σY), yield strain (εY) and hardening coefficient (H) equal to105 GPa, 900 MPa, 8.57×10−3 and 2.41 GPa, respectively.…”
Section: Femmentioning
confidence: 99%
“…The rod geometry was used to define the direction of the pullout or push-in force because its curvature constitutes the spine curvature after the surgical treatment of scoliosis. The rod geometry was approximated by quintic polynomial function using the previous method [ 13 ]. A tangent angle β that is orthogonal to the pullout or push-in force axis was computed by evaluating the derivative of quintic polynomial function evaluated for location of each screw.…”
Section: Femmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, biomechanical comparison of alternative screw densities for AIS has indicated that increased numbers of pedicle screws did not provide a higher degree of correction. 26,32 Furthermore, an international consensus suggested that an implant density less than 80% was optimal (73% vs 27%) for moderate curves with a Cobb angle of 40°-70°. 5 As to sagittal correction, pooled data on thoracic kyphosis were available in 8 studies, involving a total of 475 patients, and no significant differences were found (p = 0.26, I 2 = 79%).…”
Section: Discussionmentioning
confidence: 99%